2014
DOI: 10.6004/jnccn.2014.0127
|View full text |Cite
|
Sign up to set email alerts
|

Genetic/Familial High-Risk Assessment: Breast and Ovarian, Version 1.2014

Abstract: During the past few years, several genetic aberrations that may contribute to increased risks for development of breast and/or ovarian cancers have been identified. The NCCN Guidelines for Genetic/Familial High-Risk Assessment: Breast and Ovarian focus specifically on the assessment of genetic mutations in BRCA1/BRCA2, TP53, and PTEN, and recommend approaches to genetic testing/counseling and management strategies in individuals with these mutations. This portion of the NCCN Guidelines includes recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
179
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(186 citation statements)
references
References 12 publications
3
179
1
2
Order By: Relevance
“…Patients carrying these pathogenic variants are considered to be at a high-risk in developing tumor recurrence or secondary cancer according to the NCCN guidelines [9,34]. However, contralateral mastectomy or oophorectomy for these patients is currently not recommended in China, and asymptomatic women carrying pathogenic variants usually prefer not to undergo preventive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients carrying these pathogenic variants are considered to be at a high-risk in developing tumor recurrence or secondary cancer according to the NCCN guidelines [9,34]. However, contralateral mastectomy or oophorectomy for these patients is currently not recommended in China, and asymptomatic women carrying pathogenic variants usually prefer not to undergo preventive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We enrolled 80 of 108 consecutive patients diagnosed with breast cancer who were addressed for the oncological examination in Oncosurg Surgical Oncology Clinic, from Cluj-Napoca between January 2015 and December 2016 and met the 2016 National Comprehensive Cancer Network (NCCN) criteria for genetic testing [11]. All the patients had a histopathological diagnosis carried out through a Tru-Cut Needle Biopsy in our clinic.…”
Section: Patientsmentioning
confidence: 99%
“…In one study, 21% (9/43) of palliative oncology patients were identified as having strong genetic risk according to published criteria [7,33,38] but none had undergone genetic counselling, genetic testing or DNA storage [36]. In a survey of 49 oncology and palliative physicians, none had arranged DNA storage for patients within the last year, and 20% (10/49) commented that they had never assessed a patient's familial risk [37].…”
Section: Practice Barriersmentioning
confidence: 99%